Reconstructing the Place Memory of Buca Levantine Settlement - Yılmaz Saygın, Nicel (ICONARCH International Congress of Architecture and Planning, 2017)
The “Old Buca” (Izmir), a designated Urban Conservation Site, holds a significant place in history as originally it was one of the Levantine settlements of the late Ottoman Empire. Historically, Buca (Boudja) environs was a fertile area with vast vineyards, where a Greek village was once located. Then it became a summer resort of the Levantine families. Following the railway construction connecting the port of Izmir (Smyrna) to the city’s countryside in early 1860s, a rail line extension to Buca speeded up more Levantine families settling in Buca that made it into a commuter suburb (banlieue). Largely residential use of two storey houses within gardens, together with some religious facilities of a monastery, a bishop school, a nuns’ school and dormitories as well as churches, dominated the district originally. Later, the Levantine inhabitants were largely replaced by Turkish population. Altough only very few Levantine families remained in Buca and some of the Levantine Mansions and religious facilities have been replaced with new uses, the neighborhood still has considerable number of Levantine heritage in good state. There are several studies on “Old Buca” pointing out the architectural characteristics of the individual Levantine mansions, but this paper claims its significance as a historic district which derives from its spirit of place. Even today, when one steps into the Buca Historic District, it is easy to grasp a particular ambience and a significant sense of place that derives from its rich history. Although new users and some new uses had been introduced into the area throughout time, rich historic traces are still present in the urban fabric and layout of the streets, as well as in the memory of local people. This study claims to rediscover the spirit of place and its significance as a historic district, while it anticipates to explore the discontinuties and interruptions in urban memory. This is achieved through an investigation of powerful signs (urban reminders) that are still embedded within its urban fabric, examination of city archives consisting of maps and aerial photography and pictorial resources, exploration of old street names, and locals’ memories, particularly remaining Levantines and elderly residing in the historic district over 60 years.